Variabilidade espacial e temporal da fosfatase ácida em latossolo vermelho sob sistema plantio direto - Lobato, Guilherme Rechden (2023)
Soil is the foundation of agricultural production, providing the essential nutrients for plant growth and, consequently, feeding humans and animals. The integrity and vitality of the soil are imperative to maintain sustainable agricultural production. In a world with increasing challenges such as population demand and diminishing resources, the importance of healthy terrestrial ecosystems becomes even more pronounced. Biological indicators, particularly the activity of acid phosphatase, have been valuable tools to assess this health. In this study conducted in Cruz Alta, RS, Brazil, data on the activity of acid phosphatase in no-till areas were obtained. The fluctuation of enzymatic activity throughout the seasons was noteworthy, with a particular emphasis on data dispersion in May, showing a standard deviation of 176.6561 μg p-nitrophenol g soil-1 h-1, compared to 137.4682 μg p-nitrophenol g soil-1 h-1 in December. The variation coefficients reflected this trend, with 47.06% in May and 35.49% in December. Additionally, in the semivariogram analysis, the Gaussian model was applied, with amplitudes ranging between 28.3 meters and 16.6 meters. The regression accuracy, indicated by the R², showed values of 0.745 and 0.756 for the winter and summer seasons, respectively. These results underline the need for constant monitoring and adjustments in agricultural practices. Further studies are essential to adapt and improve sustainable strategies, ensuring the efficient use of soils and their long-term preservation.